Executive Committee Minutes 2017-04-28 - Academic Senate:::::::::
Agenda – Approved. Minutes 3/30 and 4/13 – Approved. Chair Report. President Report. Revision to the Single Subject Credential Program – approved for Senate consent calendar. Revision to the Global Studies major and minor – approved for Senate consent calendar. Statewide Senator Report. Off site location for Business degree completion at College Marin referred to all Standing Committees. Revision to the Student Grievance policy approved for the Senate agenda. Senate agenda approved.